2014
DOI: 10.1007/s12210-013-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Asbestiform tremolite within the Holocene late pyroclastic deposits of Colli Albani volcano (Latium, Italy): occurrence and crystal chemistry

Abstract: This work relates the occurrence and the characterization of fibrous tremolite within the latest pyroclastic deposits of the Colli Albani (Alban Hills) volcano, to the south-east of Rome (Italy). These mineralizations were observed during a systematic rock-sampling undertaken to complete the geological survey for the new 1:50 000 map of this volcanic area. The examined specimens were collected inside distal deposits correlated to the last Albano Maar activity, which are geographically located within the bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Details on how the exact position of the bands observed in the OH-stretching spectra of amphiboles can be used as a tool for their characterization can be found is a vast body of literature (see [21,32] for a complete list of references). Specifically, applications to the study of fibrous amphiboles can be found in References [8,26,33].…”
Section: Vibrational Spectroscopy Applied To the Crystal Chemistry Ofmentioning
confidence: 99%
“…Details on how the exact position of the bands observed in the OH-stretching spectra of amphiboles can be used as a tool for their characterization can be found is a vast body of literature (see [21,32] for a complete list of references). Specifically, applications to the study of fibrous amphiboles can be found in References [8,26,33].…”
Section: Vibrational Spectroscopy Applied To the Crystal Chemistry Ofmentioning
confidence: 99%